2007
DOI: 10.1111/j.1744-313x.2007.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐12B‐3′UTR polymorphism in association with IL‐12p40 and IL‐12p70 serum levels and silicosis severity

Abstract: Susceptibility to silicosis and to disease severity is in part genetically determined. In this study, the role of IL-12B-3'UTR polymorphism in susceptibility and severity of silicosis and its influence on IL-12p40 and IL-12p70 serum level were investigated. The quantity of IL-12p40 and IL-12p70 was detected by enzyme-linked immunosorbent assay and the genotype of IL-12B was determined using the polymerase chain reaction-restriction fragment-length polymorphism method. We observed elevated IL-12p40 in contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
6
15
0
Order By: Relevance
“…The same dependence was observed for IL-12p40 serum levels and this was reported in our previous study (Stanilova et al, 2007). However, serum levels of IL-23 and IL-12p70 were not associated with severity of silicosis.…”
Section: Tnf-a Il-12p40 Il-12p70 and Il-23 Levels In Respect To Sevsupporting
confidence: 85%
See 1 more Smart Citation
“…The same dependence was observed for IL-12p40 serum levels and this was reported in our previous study (Stanilova et al, 2007). However, serum levels of IL-23 and IL-12p70 were not associated with severity of silicosis.…”
Section: Tnf-a Il-12p40 Il-12p70 and Il-23 Levels In Respect To Sevsupporting
confidence: 85%
“…Kapachi et al (1995) reported that TGF-b or PDGF also have pro-fibrotic activity and Huaux et al (2002) indicated the profibrotic properties of IL-12p40. Although the impact of IL12p40 and IL-12Bpro genotype on silicosis development and progression was present in our previous studies, here we establish an additive and synergist effect of TNF-a and IL-12p40 in silicosis (Stanilova et al, 2007;Stanilova et al, 2008). Furthermore, we broaden our understanding of silicosis pathogenesis including evaluation of IL-23, which contains the same IL-12/ 23-p40 subunit paired with specific IL-23p19 subunit.…”
Section: Discussionmentioning
confidence: 49%
“…In this study, g.2770C [ A in the 3 0 UTR of AnMSTN has extremely significant associations with TL, BL and BW (P \ 0.01) in hatched population of bighead carp. These results support the previous findings that non-coding regulatory variants are more frequently in complex traits [35][36][37][38][39][40]. Significant association between g.2770C [ A and three growth traits in the present study may be explained by two hypotheses, as suggested by Lynch and Walsh [14].…”
Section: Discussionsupporting
confidence: 93%
“…The minor allele carriers of the IL-12Bpro promoter polymorphism were associated with a protection against susceptibility to silicosis. This was attributed to the higher production of IL-12p40 in homozygous wild-type patients (Stanilova et al, 2008). As demonstrated for other occupational lung diseases, HLA alleles were also found to be related to silicosis pathogenesis.…”
Section: Silicosismentioning
confidence: 93%
“…IL-12p40 SNPs were also studied in silicosis for their potential influence on inflammatory response by affecting Th1/Th2 cytokine balance. Stanilova et al found an association between IL-12BA/C 3 0 UTR SNP and silicosis severity in Bulgarian miners (Stanilova et al, 2007). The minor allele carriers of the IL-12Bpro promoter polymorphism were associated with a protection against susceptibility to silicosis.…”
Section: Silicosismentioning
confidence: 98%